Factors Affecting Maternal Behavior in Achieving Complete Basic Immunization for Toddlers Aged 12–23 in Banggai Laut Regency, Indonesia - Amrin Madolan; Ridwan M Thaha; Muhammad Syafar; Sudirman Nasir; Nurhaedar Jafar; A Arsunan Arsin (National Journal of Community Medicine)
Background: Complete Basic Immunization (CBI) is essential to prevent vaccine-preventable diseases (VPDs). However, the coverage of complete basic immunization in Banggai Laut Regency remains low at 67.9%, compared to the national target of 90%. Several factors, including maternal knowledge, attitudes, accessibility to healthcare facilities, healthcare workers' roles, family support, and maternal occupation, are believed to influence maternal behavior in immunization provision. This study aimed to analyze factors affecting maternal behavior in achieving complete basic immunization for toddlers aged 12–23 months in Banggai Laut Regency.